2018
DOI: 10.1051/metal/2018044
|View full text |Cite
|
Sign up to set email alerts
|

Influence of profile indicators of hot-rolled strip on transverse thickness difference of cold-rolled silicon steel

Abstract: In order to evaluate the transverse thickness difference of cold-rolled strips according to the information of hot-rolled strips and scientifically guide the setting of the indicators of the hot-rolled silicon strip, the influence model about the relation of the transverse thickness difference of cold-rolled strip to the profile indicators of hot-rolled strip is established in this paper based on simulation results. The transverse thickness difference of cold-rolled strip predicted based on the influence model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In truth, the original data always comprise lots of noise and outliers, which may bring about misleading predictions. In addition, the predicted data based on the prediction model have strong correspondence to the measured data [22]. In the Fig.…”
Section: Fig5 Framework Of Strip Crown Predictionsupporting
confidence: 52%
“…In truth, the original data always comprise lots of noise and outliers, which may bring about misleading predictions. In addition, the predicted data based on the prediction model have strong correspondence to the measured data [22]. In the Fig.…”
Section: Fig5 Framework Of Strip Crown Predictionsupporting
confidence: 52%
“…A full set of VCR configuration of seven stands for finishing rolling can maintain the stability of finishing rolling profile and improve roll wear and strip steel section quality, so that local profile defects of strip are effectively suppressed. 3. SVT work roll is adopted to cooperate with the long stroke intelligent shifting technology in the downstream stands to maximize the uniform roll wear, directly control the shape of the strip edge, reduce the crown and edge drop of the strip at the exit of finishing rolling, and improve the crown hit ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [2] believed that the hot-rolled shape of silicon steel affects the size of cold-rolled strip steel; on this basis, the proposed rectangular section control technology is a solution of silicon steel strip shape (including crown, wedge, local peak point, and flatness) throughout the whole process of strip rolling: the hot tandem rolling process includes high-performance variable crown work roll technology in the upstream stands and limited shifting technology for scheduling-free rolling in the downstream stands, while the cold continuous rolling process includes edge varying contacts work roll technology, as well as strip edge-drop setting and closed-loop control technology. Ma et al [3] analyzed the influence of the section shape of hotrolled silicon steel strip on transverse thickness difference of cold-rolled finished strip. The traditional shape control of the silicon steel strip is close to the process of finished strip steel-cold rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…Abdelkhalek et al [33] reported that the edge drop causes a slight decrease in wavelength during the cold thin strip rolling. The transverse thickness difference of the cold-rolled strip increases nonlinearly with the wedge of the hot-rolled strip [5]. Therefore, the quantitative study about the effects of entry strip edge drop or even wedge on strip flatness will be carried out in future work.…”
Section: The Strip Crown Inheritance Factor At Stands S1 and S5mentioning
confidence: 99%
“…Zhang et al [3] and Yu et al [4] discovered that increasing the entry strip crown causes an increase in the exit strip crown and the edge drop in a universal crown control mill (UCM mill) and a 20-high Sendzimir mill, respectively. Ma et al [5] carried out a numerical analysis about the influence of the hot-rolled strip profile on transverse thickness difference (TTD) of cold-rolled silicon steel, and found that the TTD of the cold-rolled strip has a nearly linear relationship with the C 40 (crown at 40 mm from the strip edge) of the hot-rolled strip without wedge, while the TTD of cold-rolled strip increases nonlinearly with the W 40 (wedge at 40 mm from the strip edge) at a certain C 40 . Using the same method, Wang et al [6] also found that the TTD of cold-rolled strip increases with the C 25 (crown at 25 mm from the strip edge) of the hot-rolled strip when the C 40 remains constant and the ratio of C 40 to C 25 varies.…”
Section: Introductionmentioning
confidence: 99%